THE INFLUENCE OF THE PRODUCT, THE PRICE AND PROMOTION OF THE DECISION OF THE PURCHASE OF TOYOTA AVANZA ON PT NASMOCO GOMBEL SEMARANG - Evan Rathomy; Rodhiyah Rodhiyah; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2016)
Decision making consumers involves the intergration combining knowledge to evaluate two or more alternative behavior and choose the one of them. Many factors that must be considered in the decision to buy a product for consideration in decision making. Departing from consideration of for decision purchase, few customers choose car products other similar since goods was more offer design for affordable more dynamic and abreast of developments. This means that declining sales Avanza at PT. Toyota Gombel Semarang. Research purposes is to analyze the influence of products, price, and promotion of the decision to buy Toyota Avanza in PT. Nasmoco gombel semarang. The population research is customers toyota has bought avanza unit in nasmoco gombel semarang about 701 a person of years of 2011 until 2013. Sampling using slovin formula so that the number of samples used in this study as many as 100 people. Data were analyzed using test validity, reliability, simple linear regression analysis, multiple regression analysis, the coefficient of determination, t-test and F test calculation using the computer program SPSS version 23 for Windows. The results showed that the product t count variable ( 7,336 ) t table ( 1,984 ) so ho turned down and ha accepted that is a difference between variables the purchase of the decision, the price t count variable ( 5,766 ) t table ( 1,984 ) so ho turned down and ha accepted that is a difference between variables of the decision purchase price, the variable t count promotion ( 6,678 ) and t table ( 1,984 ) so ho turned down and ha accepted that is a difference between variables promotion of the decision purchase , the variable f count product , price , and promotion of 19,806 f table of 2,70 so ho turned down and ha accepted that means simultaneously, products, price, and promotion significant of the decision purchase. Conclusions research is variable products have leverage on variables decision purchase, variable prices have leverage on variables decision purchase, variable promotion have leverage on variables decision purchas , and variable product, price, and promotion have leverage of the decision purchase. Advice provided for products were PT. Toyota astra motor should remain evaluate and development periodically so in the eyes of consumer products will better. The price, PT. Nasmoco gombel should stay esteem worthy the consumers are based on incomes and the competition a family car. For the promotion of companies should keep the promotion and story products more accurate given the current competition a family car more stringent.